KAJIAN EMPIRIS KEADILAN ORGANISASI, KOMITMEN ORGANISASIONAL, KINERJA KARYAWAN DAN KUALITAS PELAYANAN - Saefullah, Encep; Salapudin, Salapudin (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The purpose of this research is to be able to determine and analyze organizational justice towards service quality, organizational commitment to service quality and employee performance towards service quality at PT X Serang. This research used the Structural Equation Model-Partial Least Square (SEM-PLS) approach and involved data collection by distributing questionnaires to 33 employees with a sampling technique using non-probability sampling and assisted by the use of SmartPLS 3.2 software as a data analysis tool. The research results show that the factors of organizational justice, organizational commitment, and employee performance have a positive and significant effect on service quality based on a p-value that is smaller than 0.05